Anaesthetic Management of Ischemic Heart Disease patient for Total Abdominal Hysterectomy under Epidural Anaesthesia and Analgesia - Amarkhed Preeti2, Modi Basavaraj1*, Singh G. Naveen1 (Recent Research in Science and Technology, 2011)
Anaesthetic management of cardiac patient’s coming for non cardiac surgery has always been challenging. Goal of anaesthesia management is to keep myocardial oxygen supply greater than demand to avoid ischemia. Choice of anaesthesia has been general anaesthesia (GA) by achieving the goals, in order to prevent ischemia intra and post operatively in cardiac patient coming for non cardiac surgery. In this case report anaesthetic implications included assessment of cardio vascular status of the patient pre operatively with selection of epidural anaesthesia and analgesia technique. Incremental doses of local anaesthetic (LA) were given keeping in mind, myocardial oxygen supply to be greater than demand to avoid ischemia. To the best of our knowledge, there have been only few case reports on epidural anaesthesia for ischemic heart disease (IHD) patient coming for non cardiac surgery. Hence we report a successful anaesthetic management of a patient with ischemic heart disease for total abdominal hysterectomy under epidural anaesthesia and analgesia.